2020
DOI: 10.1186/s12885-020-07420-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-beta enhances sensitivity to gemcitabine in pancreatic cancer

Abstract: Background Adjuvant gemcitabine for pancreatic cancer has limited efficacy in the clinical setting. Impaired drug metabolism is associated with treatment resistance. We aimed to evaluate the chemosensitising effect of interferon-beta (IFN-β). Methods BxPC-3, CFPAC-1, and Panc-1 cells were pre-treated with IFN-β followed by gemcitabine monotherapy. The effect on cell growth, colony formation, and cell cycle was determined. RT-qPCR was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Our discovery that exogenous IFNβ rescued ISG expression in oncogenic models suggests that cotreatment of ionizing radiation, genotoxic drugs, and epigenetic inhibitors with T1IFN could re-sensitize these pathways for broader therapeutic reach. Several studies have reported increased efficacy using combination treatments with interferon ( 91 , 92 , 93 ). However, researchers have found that one mechanism of acquired radioresistance is through selection for insensitivity to interferon.…”
Section: Discussionmentioning
confidence: 99%
“…Our discovery that exogenous IFNβ rescued ISG expression in oncogenic models suggests that cotreatment of ionizing radiation, genotoxic drugs, and epigenetic inhibitors with T1IFN could re-sensitize these pathways for broader therapeutic reach. Several studies have reported increased efficacy using combination treatments with interferon ( 91 , 92 , 93 ). However, researchers have found that one mechanism of acquired radioresistance is through selection for insensitivity to interferon.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data revealed that the efficacy of multiple anti-tumor therapies depended on the cGAS-STING pathway activation, especially clinical immunotherapy [39]. IFN-β was originally identified as one of the immunomodulatory cytokines because of its antiviral activity [40]. As a downstream signal of cGAS-STING, IFN-β expression was discovered to be STING-dependent [37].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that TAM infiltration in PDAC cells depends on the expression of CCR2 and ZEB1, of which CCL2 and CD74 determine poor prognosis ( 38 ). An important process in the therapeutic resistance of PDAC is the interaction between TAMs and cancer stem cells (CSCs), that is, TAMs can be recruited into TME to regulate the start-up state of pancreatic CSCs ( 39 ), which secrete IFN-β ( 40 ) and other factors to stimulate TAMs to maintain the active state, thus initiating the proliferation and differentiation effect of tumor cells. TAMs can express more Arg1 to interfere with the metabolism of effecting T cells, and TGF-β, IL-10, prostaglandin E2 (PGE2) and other factors released by TAMs can help Tregs recruit and inhibit CD8+T cells ( 41 , 42 ).…”
Section: Immunosuppressive Associated Cells During the Progression Of...mentioning
confidence: 99%